CYTOKINES CHANGES ASSOCIATED WITH MENSTRUAL CYCLE IN HIV INFECTED FEMALES AT NAUTH, NNEWI, SOUTH-EAST NIGERIA - Ukibe, Nkiruka .R.; Ukibe, Solomon .N.; Emelumadu, Obiagel F.; Ifeadike, Chigozie. O.; Onyenekwe, Charles.C.; Ahaneku, Joseph .E.; Ilika, Linus .A. (European Scientific Journal, ESJ, 2015)
Background: HIV infection is characterized by hormonal and immunological changes which may grossly affect the reproductive cycle in affected women. Aim: To evaluate Cytokine changes in HIV infected women during menstrual cycle. Materials and methods: A total of 90 women aged between 15 and 45 years were randomly recruited for the study. 30 of the women were normal healthy seronegative for HIV and served as control. Blood samples were collected under sterile conditions during the follicular and luteal phases of menstrual cycle after due informed consent had been obtained and the samples were analyzed for Cytokines (IL-8, IL-6, IL-4, and TNFÎ±) using Enzyme Linked Immunosorbent Assay (ELISA) method. Results: The Cytokines (IL-8, IL-6, IL-4 and TNFÎ±) were significantly higher at both phases of menstrual cycle in HIV infected women when compared with the Control (P<0.05). Interpretation and Conclusion: The study showed significant cytokine changes with some degree of inflammatory reactions in HIV infected women. The implication of these changes within reproductive life of the women is discussed.